2007
DOI: 10.1089/jir.2007.0050
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Ingestion Does Not Alter Cytokine Changes in Athletes Competing in the Western States Endurance Run

Abstract: Initial phenotypic studies in a mouse containing mutations in both toll-like receptor 3 (TLR3) and RNA-de-pendent protein kinase R (PKR) revealed comparable spleen and bone marrow cell populations in tlr3(-/)-, pkr(-/-), and tlr3(-/-)pkr(-/-) mice to wild-type controls. Splenomegaly developing between 8 and 10 weeks of age was observed in tlr3(-/-) and tlr3(-/-)pkr(-/-) mice but not in wild-type or pkr(-/-) mice. Palpably enlarged cervical, axillary, and inguinal lymph nodes accompanied by enlarged spleens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 37 publications
3
110
2
2
Order By: Relevance
“…A few studies have evaluated the effect of exercise on MCP-1 (15,34,35) but all have observed increased MCP-1 levels in response to exercise, in contrast to the observations of the present study. Also, studies are scarce concerning the effect of exercise on IFN-γ and IL-12, two proinflammatory cytokines.…”
Section: Discussioncontrasting
confidence: 99%
“…A few studies have evaluated the effect of exercise on MCP-1 (15,34,35) but all have observed increased MCP-1 levels in response to exercise, in contrast to the observations of the present study. Also, studies are scarce concerning the effect of exercise on IFN-γ and IL-12, two proinflammatory cytokines.…”
Section: Discussioncontrasting
confidence: 99%
“…However, supplementation at higher doses (1g/day) of quercetin for 3 weeks in ultramarathon athletes before a competitive 160-km race did not change M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 levels of inflammatory and oxidative indices [36]. The same authors found no change in different indices of immune function after 3 weeks of quercetin (1 g/day), but upper respiratory tract infection incidence reduced in cyclists during the 2-week period after intensified exercise [37].…”
Section: Dietary Vs Supplemental Antioxidants: Same Effectiveness?mentioning
confidence: 90%
“…The average ⌬C T for placebo-treated mice was used as the calibrator. ⌬⌬C T [⌬CT (calibrator) Ϫ ⌬CT (sample)] was then calculated for each sample, and relative quantification was calculated as 2⌬⌬C T. Initial exclusion criteria consisted of FAM C T Ն40 and VIC CT Ն23 (18,19).…”
Section: Methodsmentioning
confidence: 99%